Integration of LwIP Stack over Intel(R) DPDK for High Throughput Packet Delivery to Applications - Rajesh, R.; Ramia, Kannan Babu; Kulkarni, Muralidhar (2014 Fifth International Symposium on Electronic System Design, 2014)
Performance of generic operating system like Linux based IP stacks on multicore processors is much less than that of the purpose built IP stacks from the commercial stack vendors which typically run on a SoC/ASICs/Network processor. The issue of under-utilization of hardware resources arises from the fact that the generic IP stacks operate with much higher overhead, thereby decreasing the overall system performance compared to the capability of the underlying hardware. With Intel multicore processors, it's possible to transition from using discrete architectures per major workload (application, control, packet, and signal processing) to a single architecture that consolidates the workloads into a more scalable and simplified solution. This is possible, in large part, due to the Intel Data Plane Development Kit (Intel DPDK), a set of data plane libraries that can improve packet processing performance by up to ten times compare to processing capabilities by traditional OS. Users can integrate their own custom IP stacks with the Intel DPDK and get the advantage of accelerated performance of the Intel DPDK to their applications. This paper explains integration of a version of Light Weight TCP/IP (LwIP) stack with Intel DPDK to extend high packet processing capabilities of Intel DPDK to application layer level and measuring the performance capabilities of DPDK-LwIP network stack.